Does skill assessment support national selection process? - Rumpf, M.; Cronin, J. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The utilization of physical testing in talent identification is questionable, given the relative age effect and therefore the utilization of other assessments needs to be considered. The purpose of this study was to investigate whether physical and/or skill assessments support the predetermined selection/non-selection of national male U17 players. Methods Fifty-five male players born within the first year of the World Cup Cycle (1994-1995), with an average height of 175.1 cm, average weight of 66.4 kg and an average maturation offset of 2.0 years, were tested for 20 meter sprint time, horizontal jump performance, Yo-Yo intermittent recovery test level 1, years of structured football experiences and on a battery of skills. The skill assessment consisted of four different rubrics - proactive passing and one-touch-play, vision and awareness, receiving and turning efficiency and proactive defending. Prior to the national camp, all coaches participating in the camp were briefed and trained to use the skill assessment tool on the players. The U17 national coach selected the wider squad players mainly after visiting the camp and was not aware of the assessment scores of all players. Results & Discussion No significant differences (p > 0.05) were found between the selected (N = 22) versus nonselected players (N = 32) for all variables except the Yo-Yo and the four skill assessments. Players who were selected for the national squad scored higher on the Yo-Yo test (p = 0.019, CI = 0.99) and all rubrics of the skill assessment (p = 0.001-0.007, CI = 0.99). It appears that aerobic fitness and skill assessment can be used as a tool to distinguish between selected and non-selected players in a national environment, based on the selection by the national coach, for subjects with equal height, weight, maturation, sprint and jump performance. However, accounting for those characteristics does not prevent selection bias over a World Cup Cycle for male football players, i.e. relative age effect. Conclusion Even though those selected were older, more mature and for the most part born in the first sixth month of the year, anaerobic tests (sprint and leg power) could not differentiate between selected versus non-selected players. However, aerobic fitness and competency on a number of skills predict/supports national selection process.